The tumor microenvironment and triple-negative breast cancer aggressiveness: shedding light on mechanisms and targeting. (2nd December 2022) - Furukawa, Natsuki; Stearns, Vered; Santa-Maria, Cesar A.; Popel, Aleksander S.
ABSTRACT: Introduction: In contrast to other breast cancer subtypes, there are currently limited options of targeted therapies for triple-negative breast cancer (TNBC). Immense research has demonstrated that not only cancer cells but also stromal cells and immune cells in the tumor microenvironment (TME) play significant roles in the progression of TNBC. It is thus critical to understand the components of the TME of TNBC and the interactions between the various cell populations. Areas covered: The components of the TME of TNBC identified by single-cell technologies are reviewed. Furthermore, the molecular interactions between the cells and the potential therapeutic targets contributing to the progression of TNBC are discussed. Expert opinion: Single-cell omics studies have contributed to the classification of cells in the TME and the identification of important cell types involved in the progression and the treatment of the tumor. The interactions between cancer cells and stromal cells/immune cells in the TME have led to the discovery of potential therapeutic targets. Experimental data with spatial and temporal resolution will further boost the understanding of the TME of TNBC.